Bladder-sparing management for high grade noninvasive urothelial carcinoma of the prostate - Martin, Alexander C.; McElree, Ian M.; Mott, Sarah L.; Hougen, Helen Y.; Steinberg, Ryan L.; O'Donnell, Michael A.; Packiam, Vignesh T. (Urologic oncology, 2025)
•Intravesical therapy can be effective for prostatic urethral urothelial carcinoma.•No statistically significant difference between Gem/Doce and BCG therapy.•No predictive factors identified associated with high grade recurrence.•Most high-grade recurrence occurs within 6 months, moderate progression rates.•Low cystectomy rate; those disease free at 1 year have more durable response. To characterize the oncologic outcomes in patients with high-grade noninvasive urothelial carcinoma of the prostate (NMIUC-P) treated with intravesical therapy and assess for clinicopathologic features associated with response. Patients with high-grade NMIUC-P treated with intravesical Bacillus Calmette-Guerin (BCG) or chemotherapy between 2005 and 2021 were retrospectively analyzed. Survival probabilities were estimated using the Kaplan-Meier method. Cox regression was used to evaluate the effect of clinicopathologic and treatment characteristics on high-grade recurrence-free survival (HG-RFS) and progression-free survival (PFS). A total of 62 patients with median follow-up of 38 months (IQR 19–74) were included. NMIUC-P pathology was carcinoma in situ containing in 52 (84%), high-grade Ta in 9 (14%), and high-grade T1 in 1 (2%). Fifty (80%) patients had concomitant bladder UC. Induction regimens were BCG (44%), gemcitabine/docetaxel (42%), and other chemotherapies (14%). HG-RFS was 45%, 43%, and 38% at 1, 2, and 3 years, respectively. Seventeen patients (27%) underwent cystectomy at a median of 12 months, of whom 5 (29%) had ≥T2 and 3 (18%) had N+ disease. Among all patients, PFS was 87%, 69%, and 69% at 1, 2, and 3 years, respectively. Cystectomy-free, cancer-specific, and overall survival were 65%, 92%, and 83% at 3 years, respectively. No clinicopathologic or treatment characteristics were significantly associated with HG-RFS. In a high-risk cohort of patients with NMIUC-P, a select number of patients were able to avoid cystectomy and remain recurrence-free at 3-years after pursuing bladder-sparing intravesical treatment. However, given the high incidence of disease progression, careful patient selection is critical. Further prospective studies are needed to identify markers of response.